Experimental Study of the Adsorption of Nitrogen and Phosphorus by Natural Clay Minerals - Tingyu Fan; Miao Wang; Xingming Wang; Yingxiang Chen; Shun Wang; Hongbin Zhan; Xiaoyang Chen; Akang Lu; Shijiao Zha (Adsorption Science & Technology)
Nitrogen and phosphorus are commonly recognized as causing eutrophication in aquatic systems, and their transport in subsurface environments has also aroused great public attention. This research presented four natural clay minerals (NCMs) evaluated for their effectiveness of NH4+ and PO43- adsorption from wastewater. All the NCMs were fully characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), BET analysis, and adsorption kinetics and isotherms to better understand the adsorption mechanism-property relationship. The results show that the adsorption efficiency of the four NCMs for phosphate was better than that for ammonia nitrogen. The removal rate of phosphate was higher than 65%, generally in the range of 80%-90%, while the removal rate of ammonia nitrogen was less than 50%. The adsorption kinetic behavior followed the pseudo-second-order kinetic model. The ammonia nitrogen adsorption isotherm was in good agreement with the Freundlich isotherm equilibrium model, and the phosphate adsorption isotherm matched the Langmuir model. Among all the NCMs studied, bentonite (7.13 mg/g) and kaolinite (5.37 mg/g) showed higher adsorption capacities for ammonia nitrogen, while zeolite (0.21 mg/g) and attapulgite (0.17 mg/g) showed higher adsorption capacities for phosphate. This study provides crucial baseline knowledge for the adsorption of nitrogen and phosphate by different kinds of NCMs.